On the intrinsic reactivity of highly potent trypanocidal cruzain inhibitors - Bonatto, Vinicius; Batista, Pedro Henrique Jatai; Cianni, Lorenzo; De Vita, Daniela; Silva, Daniel G; Cedron, Rodrigo; Tezuka, Daiane Y; de Albuquerque, Sérgio; Moraes, Carolina Borsoi; Franco, Caio Haddad; Lameira, Jerônimo; Leitão, Andrei; et al. (MedChemComm, 2020)
The cysteine protease cruzipain is considered to be a validated target for therapeutic intervention in the treatment of Chagas disease. Hence, peptidomimetic cruzipain inhibitors having a reactive group (known as warhead) are subject to continuous studies to discover novel antichagasic compounds. Here, we evaluated how different warheads for a set of structurally similar related compounds could inhibit the activity of cruzipain and, ultimately, their trypanocidal effect. We first investigated in silico the intrinsic reactivity of these compounds by applying the Fukui index to correlate it with the enzymatic affinity. Then, we evaluated their potency against T. cruzi (Y and Tulahuen strains), which revealed the reversible cruzain inhibitor Neq0656 as a better trypanocidal agent (EC Y.strain 50 = 0.1 μM; SI = 58.4) than the current drug benznidazole (EC Y.strain 50 = 5.1 μM; SI > 19.6). We also measured the half-life time by HPLC analysis of three lead compounds in the presence of glutathione and cysteine to experimentally assess their intrinsic reactivity. Results clearly illustrated the reactivity trend for the warheads (azanitrile > aldehyde > nitrile), where the aldehyde displayed an intermediate intrinsic reactivity. Therefore, the aldehyde bearing peptidomimetic compounds should be subject for in-depth evaluation in the drug discovery process. Aldehyde peptide like compounds display a bivalent reactive profile and improved antichagasic potency.